2016
DOI: 10.1161/jaha.115.002566
|View full text |Cite
|
Sign up to set email alerts
|

Association of Digoxin With Interstage Mortality: Results From the Pediatric Heart Network Single Ventricle Reconstruction Trial Public Use Dataset

Abstract: BackgroundMortality for infants with single ventricle congenital heart disease remains as high as 8% to 12% during the interstage period, the time between discharge after the Norwood procedure and before the stage II palliation. The objective of our study was to determine the association between digoxin use and interstage mortality in these infants.Methods and ResultsWe conducted a retrospective cohort study using the Pediatric Heart Network Single Ventricle Reconstruction Trial public use dataset, which inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
40
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 37 publications
1
40
1
Order By: Relevance
“…Utilising data from the Pediatric Heart Network Single Ventricle Reconstruction Trial, Oster et al reported a reduced risk of interstage mortality among those receiving digoxin therapy with a reduction from 12.3%, compared to 2.9% among those on digoxin. 17 This protective impact of digoxin was also seen even among those with no history of arrhythmia. 18 Longer term follow-up questioned the net protective effect of digoxin.…”
Section: Discussionmentioning
confidence: 95%
“…Utilising data from the Pediatric Heart Network Single Ventricle Reconstruction Trial, Oster et al reported a reduced risk of interstage mortality among those receiving digoxin therapy with a reduction from 12.3%, compared to 2.9% among those on digoxin. 17 This protective impact of digoxin was also seen even among those with no history of arrhythmia. 18 Longer term follow-up questioned the net protective effect of digoxin.…”
Section: Discussionmentioning
confidence: 95%
“…Importantly, patients discharged on digoxin were found to have an HR for mortality 3.5-fold lower than those not taking digoxin. 23 The present SVR II update does not include data regarding longitudinal practice patterns. However, there are data from the National Pediatric Cardiology Quality Improvement Collaborative as well as ad-hoc data from the SVR trial that demonstrate persistent variability in the management of post-Norwood infants through Stage II.…”
Section: Understanding and Possibly Reducing Practice Variation Amongmentioning
confidence: 99%
“…These interstage programs have been credited with substantially reducing the incidence of interstage mortality. 3 How might one explain these interesting findings? Brown et al in a study using outcomes data provided through the National Pediatric Cardiology Quality Improvement Collaborative (NPC-QIC) reported on outcomes of 544 Norwood survivors without documented arrhythmias, 22% of whom were discharged on digoxin.…”
mentioning
confidence: 99%
“…This difference could not be explained by other factors evaluated by the investigators including underlying anatomy. 3 How might one explain these interesting findings? Both papers' authors note that in most centers there was variability in the percentage of patients treated with digoxin and that it is impossible to know the reasons for the use of the medication in specific patients in these retrospective series.…”
mentioning
confidence: 99%